Assessment of cycle averaged turbocharger maps through one dimensional and mean-line coupled codes - Meng, Soon Chiong (2013)
Downsizing the internal combustion engine has been shown to be an effective strategy towards CO2 emissions reduction, and downsized engines look set to dominate automotive powertrains for years to come. Turbocharging has been one of the key elements in the success of downsized internal combustion engine systems. The process of engine-turbocharger matching during the development stage plays a significant role towards achieving the best possible system performance, in terms of minimizing fuel consumption and pollutant emissions. In current industry practice, engine modeling in most cases does not consider the full unsteady analysis of the turbocharger turbine. Thus, turbocharged engine performance prediction is less comprehensive, particularly under transient load conditions. Commercial one-dimensional engine codes are capable of satisfactory engine performance predictions, but these typically assume the turbocharger turbine to be quasi-steady, hence the inability to fully resolve the pulsating flow performance. On the other hand, a one-dimensional gas dynamic turbine model is capable of simulating the pressure wave propagation in the model domain, thus serving as a powerful tool to analyze the unsteady performance. In addition, a mean-line model is able to compute the turbine power and efficiency through the conservation method and Euler’s Turbomachinery Equation. However, none of these modeling methods have been widely implemented into commercial one-dimensional engine codes thus far. The objective of this paper is to assess the possibility of numerically producing the steady equivalent cycle averaged turbocharger turbine maps, which could be used in commercial engine codes for performance prediction. The cycle-averaged maps are obtained using a comprehensive turbocharged engine model including accurate pulsating exhaust flow performance prediction. The model is validated against experimental results and effects of flow frequency on the maps are discussed in detail.